Expression of Fas ligand in liver metastases of human colonic adenocarcinomas - Shiraki, Katsuya (The National Academy of Sciences of the USA, 1997)
Fas ligand (FasL) plays a pivotal role in lymphocyte cytotoxicity and the maintenance of immunological homeostasis. Since FasL has been implicated in the existence of immunologically privileged body sites by inducing apoptosis of activated T lymphocytes, we investigated the expression of FasL in human colon cancers. We found that two out of seven primary tumors and all four hepatic metastatic tumors of surgically obtained colonic adenocarcinoma expressed FasL mRNA and protein, detected by reverse transcription-coupled PCR and by immunohistochemical staining, respectively. Expression of FasL was not detected in normal colonic epithelial cells. FasL mRNA was also expressed in some human colonic adenocarcinoma cell lines including SW480, SW1116, and LS180 cells. Cell-surface-associated FasL was detected in these human colon cancer cells by fluorescence immunocytochemical staining. In addition, the expressed FasL was demonstrated to be functional, since coculture experiments using FasL-expressing SW480 cells resulted in apoptosis of Jurkat T leukemia cells that are sensitive to Fas-mediated apoptosis, and this process was specifically inhibited by the neutralizing anti-human FasL antibody. Thus, our findings and other data suggest an alternative mechanism that enables tumors to evade immune destruction by inducing apoptosis in activated T lymphocytes. Furthermore, constitutive expression of FasL in hepatic metastatic tumors suggests that FasL may also be important in their colonization in the liver through induction of apoptosis in the surrounding Fas-expressing hepatocytes.